Uzbek National Khan Atlas - Axmedova Nodira Axad qizi (International Journal on Economics, Finance and Sustainable Development, 2022)
This article provides information about the khan atlas, the national fabric of the Uzbek people, its origin, place in the history of our country and its physical and chemical aspects.